THE ROLE OF ACCOUNTABILITY AND TRANSPARENCY IN IMPROVING PUBLIC HOSPITAL PATIENT SATISFACTION - Novrida Qudsi Lutfillah; Annisa, Alfida Rosa (Universitas Mercu Buana Yogyakarta, 2025)
Improving the quality of public health services requires strengthening transparent, accountable, fair, and responsible governance. This study aims to analyze the influence of the principles of justice, transparency, accountability, and responsibility on patient satisfaction at Mardi Waluyo Regional Hospital, Blitar City. This study uses a quantitative approach with a survey method on one hundred outpatients and inpatients. Analysis techniques include bivariate correlation tests and multiple linear regression. The results of the study indicate that all dimensions of governance have a positive relationship with patient satisfaction, with accountability as the dimension that shows the strongest relationship, followed by transparency, responsibility, and justice. Transparency and accountability are the two most determining principles, especially through openness of information, clarity of procedures, and accuracy of service implementation by medical personnel. Meanwhile, justice and responsibility are considered not to have a real impact, although they are still considered important by patients. The implications of this study indicate that the implementation of effective governance can be a primary strategy in building public trust and strengthening government hospital services that are fair, professional, and oriented towards patient satisfaction.